Government Intervention in the Economy-Test on Malaysia's Fiscal Conduct - Evan, Lau; Shazali, Abu Mansor; Puah, Chin Hong (Asia Pacific Journal of Economics and Business, 2006)
Using Malaysia as a case study, this paper investigates the conduct of fiscal policy regimes during the last three decades. Empirical results show that in pre-crisis Malaysia the fiscal stance is not sustainable, while in the full sampling period (including the post-1997 crisis era) it satisfies only the necessary condition for sustainability. Long-run oneway causation from expenditure to revenue was observed, in line with the spend-and-tax hypothesis. The Malaysian government, therefore, must aim to reduce the size of government spending and promote a costeffective expenditure program with maximum benefits, to moderate the post-crisis fiscal imbalances